REQUEST STRATEGIES USED BY THE MAIN CHARACTER OF DESPICABLE ME MOVIE - WANDIN, DIANA CHEN (Jurnal Ilmiah Mahasiswa FIB, 2013)
When people communicate with others using language, they produce speech acts. Speech acts are part of language concerning with what people say through the language, that is the meaning of utterances. One of speech acts is request which is the action of asking for something. This study focuses on classifying the request strategies used by the main character of Despicable Me movie, Gru, using Blum Kulka et al theory (1987). This study is aimed to show various request strategies that may be used by Gru in a conversation depending on the context. The problems of the study are (1) What are the types of the request strategies used by the main character of Despicable Me movie?; (2) What are the contexts that motivate the application of the request strategies used by the main character of Despicable Me movie?This research used qualitative approach because the analysis is in the form of description rather than number. Then, the research was conducted through documentary analysis since the researcher analyzed Gru’s utterances containing request strategies. The researcher collected the data by using several steps those are watching the movie, finding the transcript, reading the transcript of the movie, and selecting and listing the utterances of the main character based on request strategies. Then the researcher analyzed the contexts that motivate the application of the request strategies used by the main character of Despicable Me movie.The result of the research shows that there are seven out of nine types of request strategies used by the speaker namely (1) mood derivable, (2) performative, (3) hedged performatives, (4) obligation statement, (5) want statement, (6) query preparatory, and (7) mild hint. There are five types of context that occur in the conversation used to answer the contexts that motivate the application of the request strategies used by the main character of the movie, those are (1) physical context, (2) inner context, (3) symbolic context, (4) relational context, and (5) situational context. The finding also shows that the type of request strategies used most frequently in this movie is obligation statement. The contexts that motivate the application of the request strategies used most frequently in this movie is relational context because this movie tells about the relationship between a father and his children.Based on the result of the study, the writer wants to give suggestions for the next researcher to conduct a research in a different object of the study and different theories such as request strategies used in Bahasa Indonesia. It might have different result because of cultural differences. So, he or she may get different finding as well. Key words: Speech acts, request strategies, Despicable Me movie